2021
DOI: 10.1016/j.jhin.2021.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and impact of hospital-acquired pneumonia: a Portuguese nationwide four-year study

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Despite improvements in prevention, antimicrobial therapy, and supportive care [30], HAP remains an important cause of morbidity and mortality. HAP has been associated with significant mortality [31,32]. In our study, IHM was similar in COPD patients and in non-COPD patients, with no significant change overtime.…”
Section: Discussionsupporting
confidence: 57%
“…Despite improvements in prevention, antimicrobial therapy, and supportive care [30], HAP remains an important cause of morbidity and mortality. HAP has been associated with significant mortality [31,32]. In our study, IHM was similar in COPD patients and in non-COPD patients, with no significant change overtime.…”
Section: Discussionsupporting
confidence: 57%
“…Despite improved preventive measures, antimicrobial therapy, and supportive care [ 33 ], HAP continues to be a major cause of morbidity and mortality and has been associated with significantly high mortality [ 35 , 36 ]. In our study, IHM was similar in T2DM patients and in non-T2DM patients, with no significant change over time.…”
Section: Discussionmentioning
confidence: 99%
“…Non-ventilator hospital-acquired pneumonia (HAP) is a serious nosocomial infection that is generally under-studied compared to ventilator-associated pneumonia. Recent studies have shown that the incidence of this disease is 0.12-2.28 per 1,000 patient admissions in the U.S. acute care hospital setting and 0.95 per 100 admissions in the Portuguese National Health System hospitals (1,2). The incidence of HAP is closely related to a high mortality rate and high medical burden.…”
Section: Introductionmentioning
confidence: 99%